Peningkatan Kinerja Melalui Supervisi Akademik pada Guru SDN 118/X Pangkal Kemang Tahun Pelajaran 2019/2020 - Suriadi Suriadi (Departement of Mathematics Education, 2022)
This School Action Research aims to improve teacher performance outcomes at SDN 118/X Pangkal Kemang Kel. Rano, West Muara Sabak Sub-district, East Tanjung Jabung Regency, Jambi Province. This research is a School Action Research with the research subjects being teachers at SDN 118/X Pangkal Kemang Kel. Rano, Kec. Muara Sabak Barat, Tanjung Jabung Timur Regency, which amounted to 8 people. At the initial stage, planning is carried out to be implemented and observed and reflected, the results of the reflection are used as a reference for planning cycle II. The results of the first cycle show the average value of teacher performance with a percentage of completeness of 60%. When converted to the achievement of school KKM, the value does not meet the standard, and the percentage of completeness has not reached classical completeness. Based on the input from the observers, a second cycle plan was prepared. The results of the supervision in cycle II showed the average value of the teacher's performance results with a 91% completeness percentage and had reached classical completeness. Comparison of cycle I with Cycle II there is an increase in teacher performance results 31%. Based on these results, academic supervision of teachers at SDN 118/X Pangkal Kemang can improve teacher performance outcomes.